دراسة تحليلية عن مدى الملاءمة بين خريجي المدرسة وفرصة العمل - Asep Ahmad Fathurrahman (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2016)
The Relevance of student graduates with the job they achieved are very important. This condition meets both the the hopes and ambitions of students and parents. It goes without saying that this is one indicator of the success of education program. The study was aimed at determining the preparation of the government to implement the curriculum in 2013, investigating the strategy to build the relevance between education and work, scrutinizing students’ mindset concerning the relevance of education and work. This study used descriptive analysis which is qualitative approach in nature. The findings of this study show that the government has prepared the curriculum gradually in 2013, and the government has administered 9 years school program, some district-State has already applied the 12 years education program, as well as it has spent education funding by 20%, and it has opened the program Vocational High School (SMK). Students’ mindset graduated from SMK has shifted from job-seeking to job-creating because they have sufficient skill. The degree of relevance between what students learn and what the society need is dependent upon collaboration among all stakeholders.